Effect of Plant Spacing on Dry Matter Yield and Proximate Composition of Irrigated Columbus Grass (Sorghum almum) - Gumel, I. A.; Baba, M.; Abdurrahaman, S. I.; Ibrahim, A. A.; Babangida, I.; Kiri, I. Z.; Adamu, A. U.; Babandi, B.; Usman, I. (Nigerian Journal of Animal Science and Technology (NJAST), 2020)
An experiment was conducted to evaluate the effects of plant spacing on the dry matter yield andproximate composition of Columbus grass (Sorghum almum) under irrigation at federal universityDutse, Jigawa state. The experiment was laid out in completely randomized design (CRD)Consisting plots of 5 treatments (spacing’s) replicated in 3 blocks with 5 plots of 2x3m and 0.5 mbetween plots. The experimental area was divided in to 15 plot of 2×3 cm each, with 0.5 mpathway. The results revealed that plant height of 190.5 cm was recorded in Sorghum almum spaceat 25×20cm plant spacing. Number of leaves, number of tiller per plant were significantly affectedby spacing (p>0.05). The highest plant height (190.5cm), leaves number per plant (10leaves/plant), fresh weight leaves/stem and dry weight leaves to stem ratio were significantly(p>0.05) affected Fwl (46.3), Fws (73.0), Dwl (18.83), and Dws (26.7) The percentage proximatecomposition was not significantly (p<0.05) affected by plant spacing. The CP and CF range (6.57-6.75%), (57.1-75.2%) Ca, Mg were significantly (p<0.05) affected but percentage phosphorouswas not significantly affected. This study recorded that Sorghum almum can be best grown in25×35cm plant spacing for better yield and quality. Sorghum almum is therefore, recommendedto be grown at 25×35 plant spacing by smallholder farmers and livestock owners in Nigeria.